2011
DOI: 10.5234/cnpt.2.12
|View full text |Cite
|
Sign up to set email alerts
|

How can we classify “mood stabilizers” with different properties?

Abstract: Mood stabilizers have been conventionally defined as drugs possessing efficacy in both acute and maintenance therapy for any polarity of bipolar disorder. Only lithium has been regarded as the gold standard mood stabilizer, fulfilling all of these conditions. Recently, evidence for the comprehensive mood-stabilizing effects of second-generation antipsychotics such as quetiapine and olanzapine has been found, although their safety in long-term use is still of great concern. Antiepileptic drugs do not appear to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…First, antidepressants, especially as monotherapy, should be avoided in mixed depression since these drugs often worsen irritability, agitation and impulsivity, and increase risky behavior [16,18]. Second, instead of antidepressants, mood stabilizers possessing predominantly antimanic properties, such as valproate, carbamazepine and lithium, should be primarily used in depressive mixed state, especially in relapse prevention as opposed to acute-phase therapy, whereas monotherapy with a predominantly antidepressive mood stabilizers such as lamotrigine are not generally recommended [19,20]. Third, atypical antipsychotics, like olanzapine, quetiapine and aripiprazole, may be considered for the urgent stabilization of depressive mixed state, especially in acute-phase therapy [19][20][21].…”
Section: Therapeutic Considerations In Depressive Mixed Statementioning
confidence: 99%
“…First, antidepressants, especially as monotherapy, should be avoided in mixed depression since these drugs often worsen irritability, agitation and impulsivity, and increase risky behavior [16,18]. Second, instead of antidepressants, mood stabilizers possessing predominantly antimanic properties, such as valproate, carbamazepine and lithium, should be primarily used in depressive mixed state, especially in relapse prevention as opposed to acute-phase therapy, whereas monotherapy with a predominantly antidepressive mood stabilizers such as lamotrigine are not generally recommended [19,20]. Third, atypical antipsychotics, like olanzapine, quetiapine and aripiprazole, may be considered for the urgent stabilization of depressive mixed state, especially in acute-phase therapy [19][20][21].…”
Section: Therapeutic Considerations In Depressive Mixed Statementioning
confidence: 99%
“…Some studies that aimed to determine which agents meet the definition of MS reported that only LIT fulfilled the above definition and some have arguably achieved it prematurely [ 27 , 28 ]. More recent studies have expanded the definition of MSs to include some AAPs [ 26 , 29 , 30 ]. The results from this study could be interpreted as supporting the latter contention.…”
Section: Discussionmentioning
confidence: 99%